Specificity of Bacillus thuringiensis delta-endotoxins is correlated with the presence of high-affinity binding sites in the brush border membrane of target insect midguts. - Hofmann, C (1988)
Binding studies were performed with two 125I-labeled Bacillus thuringiensis delta-endotoxins on brush border membrane vesicles prepared from the larval midgut of the tobacco hornworm Manduca sexta or the cabbage butterfly Pieris brassicae. One delta-endotoxin, Bt2-protoxin, is a 130-kDa recombinant crystalline protein from B. thuringiensis subsp. berliner. It kills larvae of both insect species. The active Bt2-toxin is a 60-kDa proteolytic fragment of the Bt2-protoxin. It binds saturably and with high affinity to brush border membrane vesicles from the midgut of both species. The other delta-endotoxin, Bt4412-protoxin, is a 136-kDa crystalline protein from B. thuringiensis subsp. thuringiensis, which is highly toxic for P. brassicae, but not for M. sexta larvae. Bt4412-toxin, obtained after proteolytic activation of Bt4412-protoxin, shows high-affinity saturable binding to P. brassicae vesicles but not to M. sexta vesicles. The correlation between toxicity and specific binding is further strengthened by competition studies. Other B. thuringiensis delta-endotoxins active against M. sexta compete for binding of 125I-labeled Bt2-toxin to M. sexta vesicles, whereas toxins active against dipteran or coleopteran larvae do not compete. Bt2-toxin and Bt4412-toxin bind to different sites on P. brassicae vesicles.